Relationship Between Eye Pressure Level and Degree Severity of Keratitis in Patients Carry on Age: Quantitative Study at Yogyakarta - Alia Narwastu Mabrouka; Sri Wahyu Budoyo Kusumo (Cerdika: Jurnal Ilmiah Indonesia, 2025)
Keratitis represents a significant ocular health challenge among elderly populations, particularly due to age-related immune system decline and potential complications from elevated intraocular pressure (IOP). This study aims to analyze the correlation between intraocular pressure levels and keratitis severity in elderly patients. The research methodology employs a quantitative analytical approach with cross-sectional design, involving 65 elderly patients (?60 years) diagnosed with keratitis in Yogyakarta during January 2023 to December 2024. Intraocular pressure measurements were conducted using non-contact tonometry (NCT), while keratitis severity was classified according to American Academy of Ophthalmology (AAO) clinical grading guidelines into mild, moderate, and severe categories. Statistical analysis utilized Pearson correlation test and simple linear regression to assess the relationship strength and predictive contribution of IOP to keratitis severity. Research findings demonstrate a significant positive correlation between intraocular pressure and keratitis severity (r = 0.62, p < 0.001), indicating that higher IOP levels are associated with more severe keratitis presentations. Linear regression analysis reveals that IOP contributes 38.4% of the variation in keratitis severity (R² = 0.384), with each 1 mmHg increase in IOP corresponding to a 0.13-point increase in severity score. The implications of this research indicate that routine IOP monitoring should be integrated into standard keratitis management protocols for elderly patients, as elevated pressure serves as both a risk factor and prognostic indicator for disease severity. These findings support the development of comprehensive screening programs and evidence-based treatment protocols that address both corneal inflammation and pressure regulation in geriatric.